MEMBANGUN KETAHANAN SOSIAL KELUARGA DALAM KEBERAGAMAN - Khotibul Umam (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
Indonesia is a very diverse country. Diversity is reflected in many ways, ranging from ethnicity, religion, race, and culture. Indonesia's diversity starts with the diversity of individuals in the family, a diversity that cannot be denied. With diversity will make it rich for a nation, especially Indonesia, but there will likely be conflicts within the community due to the diversity that exists. Social security becomes important for a family to be able to stay and be able to solve the problems faced. The family sphere is very important as the spearhead in building social resilience in diversity. The family must be able to maintain and create social harmony, social empathy, and imbalance and non-conducive family members. Through it, social security can be realized well.Keywords: social resilience, family function, diversity